FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMAKAIAN KONTRASEPSI SUNTIK 3 BULAN DI BPM KASIH BUNDA DESA SUKADAMAI KABUPATEN MUSI BANYUASIN TAHUN 2021 - Nurul Qomariah; Syarifah Ismed; Titin Dewi Sartika (Poltekkes Kemenkes Medan, 2021)
Family Planning (KB) is an action that helps individuals or married couples to get certain objectives, avoid unwanted births, regulate the interval between pregnancies, control the time of birth in a husband and wife relationship and determine the number of children in the family. Data from the Ministry of Health of the Republic of Indonesia in 2019, the number of family planning participants in Indonesia in 2018 was 24,196,151 people (62.5%) of the number of couples of childbearing age, which was 38,690,214 people. A person's decision to use contraceptives is influenced by factors of age, education, knowledge, and number of children. Income. The purpose of this study was to determine the relationship between knowledge, age, parity and income simultaneously with the use of 3-month injectable contraceptives at BPM Kasih Bunda, Sukapeace Village, Musi Banyuasin Regency in 2021.The research design uses an Analytical Survey with a Cross Sectional approach. The population in this study were all family planning acceptors who came to BPM Kasih Bunda, Sukapeace Village, Musi Banyuasin Regency, amounting to 167 people. The number of samples in this study were 63 respondents who were taken using purposive sampling technique. Data collection using a questionnaire sheet. Data analysis using univariate analysis and bivariate analysis using chi square test.The results showed that there was a relationship between knowledge (p value = 0.028), age (p value = 0.000), parity (p value = 0.023) and income (p value = 0.004) with the use of 3-month injectable contraceptives at BPM Kasih Bunda, Sukapeace Village, Musi Banyuasin Regency. year 2021.The conclusion is that there is a relationship between knowledge, age, parity and income with the use of 3-month injectable contraceptives at BPM Kasih Bunda, Sukapeace Village, Musi Banyuasin Regency in 2021.